THE MOON REPRESENTS MY HEART - Wangtechawat, Pim (London : Magpie Books, 2023)
When Joshua and Lily meet as students in 1970s London they know right away: they've found someone who shares their secret, the one they don't even fully understand themselves. They've found another time-traveller. Exhilarated and in love, they push their gift to the limit, even after they settle down and have two children, Tommy and Eva. But when their most adventurous experiment yet goes wrong, their children are left to make their own way, even when it feels like time has stopped. Eva might be trying to move forward, but Tommy is pulled further and further back into a past that he hopes holds the truth. When he falls in love with a woman from a different era, the stability Eva has managed to carve out for them begins to crumble.
"How far would you travel to find a love lost in time?" -- Cover.
Keywords: Time travel -- Fiction; Man-woman relationships -- Fiction; Siblings -- Fiction; Interpersonal attraction -- Fiction; London (England) -- Fiction; Romance fiction; Time-travel fiction